A poética e a política no cinema de Glauber Rocha e Sembene Ousmane - Souza, Victor Martins de (2012)
We discuss the relation between Glauber Rocha and Sembene Ousmane s cinematographics and political projects considering images dialogues. The focus of our analysis is on the movies Der Leone have sept cabeças (1969-70), by Glauber, and Ceddo (1976), by Sembene. Using the technique of historians, these filmmakers problematized the present from the re-intepretation of the past. In Ceddo, Sembene reinvented traditions with the intention of questioning the history of his time, and denounced West African colonialism to be more sophisticated than previously imagined. In Der Leone have sept cabeças there exists different historical periods to question the present. In this process, the oral traditions have a preponderant role because they are used to critize the deformed European view concerning the Third World. Therefore, the relationship between the cinema of Glauber and Sembene enables us to gain a new perspective of their work, through the diasporic, tri-continental, and politically-cultural dialogue